Orthopaedic rehabilitation of the athlete getting back in the game - Davies, George J.; Provencher, Matthew T.; Reider, Bruce (Elsevier/Saunders, 2015)
Orthopaedic Rehabilitation of the Athlete was designed to be a comprehensive, extensively illustrated textbook about the rehabilitation of common musculoskeletal conditions that affect athletes-from the professional competitor to the occasional participant.